How a Company Called BlackRock Shapes Your News, Your Life, Our Future - Ben (Common Reader, 2021)
Who controls the corporations who control our news? A helpful index was just compiled—not by mainstream media, but by Harvard researchers exploring media’s future. Skimming the list, I see two names again and again: BlackRock Fund Advisors and Vanguard Group.